2006
DOI: 10.1038/sj.leu.2404471
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of RAD001 (everolimus) as a single agent and combined with other agents in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is an aggressive form of B-cell non-Hodgkin's lymphoma, with a mean survival of only 3-5 years and suboptimal therapeutic options. MCL is characterized by a balanced translocation t(11;14)(q13;q32), resulting in overexpression of cyclin D1, a G 1 cyclin regulated by the PI3K/Akt/mammalian target of rapamycin (mTOR) signaling pathway. As improved therapy for MCL is required and the mTOR pathway may be involved in its pathophysiology, the antiproliferative effects of RAD001 (everolimus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 44 publications
8
96
0
1
Order By: Relevance
“…In tumours addicted to this growth factor stimulation, chemotherapy combined with mTOR inhibition has shown synergistic anti-tumour effects. For example, data have shown that rapamycin and everolimus can enhance the antitumour activity of paclitaxel (O'Reilly et al, 2003;Mondesire et al, 2004;Faried et al, 2006;Aissat et al, 2007;Haritunians et al, 2007) in a manner related in occurrence and extent to the tumour, dose, and interestingly, the sequence of administration of the mTOR inhibitor and paclitaxel (O'Reilly et al, 2003;Mondesire et al, 2004;Faried et al, 2006;Aissat et al, 2007). In vitro, paclitaxel treatment before mTOR inhibition produced greater enhancement of apoptosis than treatment after or simultaneously with the mTOR inhibitor, which may reflect a conflict between the slowing of the cell cycle through the G 1 -S transition by mTOR inhibition and the requirement that cells be in G 2 -M transition for paclitaxelinduced apoptosis (Mondesire et al, 2004;Aissat et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In tumours addicted to this growth factor stimulation, chemotherapy combined with mTOR inhibition has shown synergistic anti-tumour effects. For example, data have shown that rapamycin and everolimus can enhance the antitumour activity of paclitaxel (O'Reilly et al, 2003;Mondesire et al, 2004;Faried et al, 2006;Aissat et al, 2007;Haritunians et al, 2007) in a manner related in occurrence and extent to the tumour, dose, and interestingly, the sequence of administration of the mTOR inhibitor and paclitaxel (O'Reilly et al, 2003;Mondesire et al, 2004;Faried et al, 2006;Aissat et al, 2007). In vitro, paclitaxel treatment before mTOR inhibition produced greater enhancement of apoptosis than treatment after or simultaneously with the mTOR inhibitor, which may reflect a conflict between the slowing of the cell cycle through the G 1 -S transition by mTOR inhibition and the requirement that cells be in G 2 -M transition for paclitaxelinduced apoptosis (Mondesire et al, 2004;Aissat et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We chose the BRC combination based on the effects of its single-agent activity and potential synergistic effect with other agents. [18][19][20] RTX has been used in clinical trials in newly-diagnosed and relapsed or refractory MCL, with ORR of 37%. 21 At M. D. Anderson Cancer Center, our upfront therapy for MCL is R-HyperCVAD/R-Methotrexate-Cytarabine.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Phase I/II clinical trials are in progress with this class of substances in various solid cancers 16 and in hematological malignancies. 17,18 In the evolution of AML, constitutive activation of the phosphoinositide-3 kinase pathway is a critical event. 19 One of the important downstream targets of phosphoinositide-3 kinase is mTOR, which mediates the effects of both BCR-ABL and FMS-like tyrosine kinase 3 (FLT3) by the regulation of protein translation through phosphorylation of its substrates, p70 S6 kinase and 4EBP-1.…”
Section: Introductionmentioning
confidence: 99%